The first patient with tandem duplication of 6q14q16: Molecular and phenotypic characterization. Issue 9 (23rd June 2016) - Sanmann, Jennifer N.; Casas, Kari A.; Bevilacqua, Jen; Bishay, Danielle L.; Clark, Tanner; Van Dyke, A. Zephyr; Leiferman, Patricia Crotwell; Reddi, Honey V.; Starr, Lois J.
Abstract : Duplications of the long arm of chromosome 6 have been previously reported in a limited number of patients; however, most reported duplications encompass regions of chromosome 6 distal to band q21. Duplications restricted to the proximal portion of 6q are rare. We report an 8‐year‐old male with a 16.4 megabase (Mb) tandem duplication of chromosome 6q14.1q16.1 (chr6:78950191‐95395865; hg19) who exhibited dysmorphic facial features, seizures, global developmental delay, intellectual disability, autism spectrum disorder, sensorineural hearing loss, and immune deficiency. This patient refines and potentially expands the current, poorly‐characterized phenotype associated with duplication of this proximal 6q region. We recommend a low threshold for a hearing evaluation beyond newborn screening and for pursuing an immune work‐up in patients with similar 6q duplications. © 2016 Wiley Periodicals, Inc.